Sex differences in perivascular adipose tissue-dependent vascular control in the porcine coronary artery - Ahmad, Abdulla A. (2018)
Research during the past decade has highlighted the functional role of perivascular adipose tissue (PVAT) in regulating the contractility of the underlying vascular smooth muscle cell layer. However, the mechanisms underlying these observations are poorly understood. As a sexual dimorphism has been identified in the regulation of vascular tone, the aim of this thesis was to determine whether there are sex differences in PVAT-mediated regulation of the porcine coronary arterial (PCA) tone. In the presence of adherent PVAT, which was stored overnight at 4Co, contractions to the thromboxane mimetic U46619 and endothelin-1 were significantly reduced in PCAs from females, but not PCAs from males. In PCAs pre-contracted with U46619, re-addition of PVAT caused relaxation in PCAs from females, but not PCAs from males. This relaxant response in coronary arteries derived from females was inhibited by a combination of both NO synthase inhibitor (L-NAME) and the cyclooxygenase inhibitor indomethacin. Pre-incubation with an anti-adiponectin antibody abolished the relaxant effects of PVAT, indicating that adiponectin is likely to be the mediator released from the fat. There was no difference in either expression or release of adiponectin from PVAT between sexes. On the other hand, the adiponectin receptor agonist adipoRon produced greater relaxation in PCAs from females compared to PCAs derived from males. No adiponectin receptor 1 expression was detected in PCAs whilst adiponectin receptor 2 and adiponectin binding protein (APPL1) were expressed equally in PCAs from both sexes. Pre-incubation with the hydrogen sulphide enzyme inhibitors 4-propargylglycine (PPG) and 2-(aminooxy)-acetic acid (AOAA) did not reduce the anticontractile responses to PVAT. Cystathionine β-synthase (CBS) and 3-mercaptopyruvate sulfurtransferase (3MPST) are expressed in PVAT from both sexes equally, with a relatively low activity, whilst no cystathionine γ-lyase (CSE) expression has been identified in PVAT from both sexes. These data indicate a clear sex difference in the regulation of coronary artery tone in response to adiponectin receptor stimulation, which may underlie the anticontractile effects of PVAT in females. Although H2S synthesizing enzymes are expressed in PVAT, they have no functional role in PVAT-induced vasorelaxation. In arteries from both male and female pigs, addition of fresh PVAT caused a contraction, which was partially inhibited by the cyclooxygenase inhibitors indomethacin and flurbiprofen. The PGF2α receptor (FP) antagonist AL8810 attenuated the PVAT-induced contractions in arteries from males, whereas the TXA2 receptor (TP) antagonist GR32191B inhibited the PVAT-induced contractions in arteries from females. Although there was no difference in PGF2α levels in PVAT between females and males, PGF2α produced a larger contraction in arteries from males, correlating with a higher FP receptor expression detected by immunoblotting. In contrast, the release of TXB2 from PVAT from females was greater than the release from males PVAT, but there was no difference in the contraction by the TXA2 agonist U46619. Furthermore, there was no difference in the role of extracellular Ca2+ and Rho kinase pathway (intracellular Ca2+) in the action of U46619, or TP receptor expression in arteries from different sexes. Pre-incubation with the reactive oxygen species (ROS) scavenger N-acetyl-L-cysteine (NAC), a non-selective NADPH oxidase (Nox) inhibitor (DPI), a selective Nox1 inhibitor (ML171), a selective Nox2 inhibitor Phox-I2 and selective Nox1 and Nox4 inhibitor (GKT137831) significantly reduced PVAT-induced vasoconstriction in PCAs from both females and males. Nox1, Nox2 and Nox4 were expressed equally in PVAT from male and females. However, in PCAs, Nox1 expression was greater in females whilst Nox4 was higher in males. Nox2 was expressed equally in PCAs from different sexes. ML171 and phox-I2 reduced superoxide anion (O2-) production in PVAT and PCAs from both sexes. GKT137831 inhibited H2O2 production in PCAs, but not PVAT, from both sexes. Both U46619 and PGF2α had similar effects on ROS production in that they did not increase O2- production in PVAT while they enhanced O2- production in PCA from females only. Functional studies showed that Nox inhibitors could inhibit the PCAs response to both U46619 and PGF2α in females only. The adipose-derived compound chemerin-9 caused a significantly higher vasoconstriction in PCAs from females in comparison with males PCAs. Similarly, chemerin-9 enhanced Nox activity in females PCAs but not in males PCAs. Chemerin mRNA was expressed in the PVAT, and the chemerin receptor ChemR23 was expressed in PCAs, although there were no sex differences. The anti-chemerin antibody can abolish the PVAT-induced contractions in both sexes. The sexual dimorphism in the contraction to chemerin could be explained by differences in the signalling downstream of the chemerin receptor in PCAs rather than the expression of chemerin or its receptor in PVAT and PCA, respectively. In conclusion, this thesis has demonstrated clear sex differences in the regulation of coronary artery tone by PVAT, with a dual effect of PVAT on the contractility of the PCA. PVAT stored overnight enhanced vasorelaxation in PCAs from females only due to the increased adiponectin activity compared to the males PCAs. In contrast, fresh PVAT augments vasoconstriction in PCAs from both sexes. Prostanoids have an important role in PVAT-induced vasoconstriction in which PGF2α and TXA2 are responsible for vasoconstriction in male and female PCAs, respectively. In addition, chemerin may have a role as a PVAT-derived contractile agent in female PCA only, while Nox-derived ROS regulates PVAT-induced contraction in the PCAs from both sexes. This study highlighted the importance of considering potential sex differences in the responses to PVAT and that sex-specific drug treatment may represent a potential strategy in the treatment of cardiovascular diseases.